Influence of Size Effect on Cutting Edge Rounding and Surface Roughness in Micro-Milling of Ti-6Al-4V. Issue 1 (May 2020) - Fakirin Ismail, Izzul; Afizi Shuaib, Norshah; Zainal Abidin, Zailani; Abdul Rahim, Irfan; Heinemann, Robert
Abstract: The quality of cutting depends most on the cutting tool condition. Towards having a good quality finish, cutting tolerance becomes a major concern, especially when machining at micro-scale where highly precise cutting is desired. This research investigates the size-effect during the micro-milling of Ti-6Al-4V under dry condition where the observations were made on cutting edge rounding (CER) and workpiece surface roughness. The result showed that the lower the feed rate, the greater rounding on the cutting edges were observed. Similar trend in result was obtained when measuring the surface roughness. The best feed rate for both observations was at 60 mm/min, where this setting has brought the mechanism to shearing, as the ratio between undeformed chip thickness and cutting edge radius started at 1.